1994
DOI: 10.1080/09639289400000029
|View full text |Cite
|
Sign up to set email alerts
|

Introducing spreadsheets into an intermediate financial accounting course: the results of a quasi-experiment

Abstract: Previous research has revealed a measurable decrease in student attitude towards the use of computers when they are integrated into teaching. This fall in attitude is thought to reflect the initial difficulties encountered when attempting to use computers and learn accounting techniques at the same time. However, it is postulated that once the students' computer ability has achieved an adequate level, then attitude will recover. This paper reports the results of a continuing investigation into the attitude of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Enquanto estudos mais antigos reportam resultados referentes ao uso de novas tecnologias para a realização de tarefas, como é o caso dos estudos que verificaram o uso de computadores e planilhas próximo do seu surgimento (Marriott, 1992;Marriott & Mellett, 1994;McInnes, Pyper, Van Der Meer & Wilson 1995), estudos posteriores analisam o uso de tecnologias que se popularizaram para apresentação de conteúdo. Especificamente no uso do PowerPoint, os aspectos positivos são de que os estudantes melhoraram sua atitude em relação ao professor que usa tal mídia e o consideram mais eficiente e eficaz quando fornece as anotações; mas efeitos do uso da mídia na memória e do fornecimento das anotações no desempenho em provas não foram confirmados (Nouri & Shahid, 2005;.…”
Section: Uso De Tecnologiasunclassified
“…Enquanto estudos mais antigos reportam resultados referentes ao uso de novas tecnologias para a realização de tarefas, como é o caso dos estudos que verificaram o uso de computadores e planilhas próximo do seu surgimento (Marriott, 1992;Marriott & Mellett, 1994;McInnes, Pyper, Van Der Meer & Wilson 1995), estudos posteriores analisam o uso de tecnologias que se popularizaram para apresentação de conteúdo. Especificamente no uso do PowerPoint, os aspectos positivos são de que os estudantes melhoraram sua atitude em relação ao professor que usa tal mídia e o consideram mais eficiente e eficaz quando fornece as anotações; mas efeitos do uso da mídia na memória e do fornecimento das anotações no desempenho em provas não foram confirmados (Nouri & Shahid, 2005;.…”
Section: Uso De Tecnologiasunclassified
“…Prior research supported the usage of spreadsheet applications in financial accounting courses. In their study of using spreadsheet application in an intermediate accounting course, Marriott and Mellett (1994) reported that “compared with manual methods […]. the spreadsheet provides increased computation accuracy” and elevates students’ competitiveness in the job market (p. 297).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of student performance, the findings from such studies have yielded mixed results (Lane and Porch, 2002). Early research on student performance has reported either: ambiguous results, indifferent performance or even a decline in performance (McInnes et al, 1995;Marriott and Mellett, 1994;Sangster, 1992). However, a higher proportion of more recent studies are indicating an improvement in students' performance as a result of using computer-assisted applications (Potter and Johnston, 2006;Davidson, 2002;Fetters et al, 1986;Friedman, 1981;Groomer, 1981;Perera and Richardson, 2010).…”
Section: Literature Review and Hypothesis Development Calmentioning
confidence: 99%